Incidence of thrombotic complications and overall survival in hospitalized patients with COVID-19 in the second and first wave. Issue 199 (March 2021) - Kaptein, F.H.J.; Stals, M.A.M.; Grootenboers, M.; Braken, S.J.E.; Burggraaf, J.L.I.; van Bussel, B.C.T.; Cannegieter, S.C.; ten Cate, H.; Endeman, H.; Gommers, D.A.M.P.J.; van Guldener, C.; de Jonge, E.; et al.
Abstract: Introduction: In the first wave, thrombotic complications were common in COVID-19 patients. It is unknown whether state-of-the-art treatment has resulted in less thrombotic complications in the second wave. Methods: We assessed the incidence of thrombotic complications and overall mortality in COVID-19 patients admitted to eight Dutch hospitals between September 1st and November 30th 2020. Follow-up ended at discharge, transfer to another hospital, when they died, or on November 30th 2020, whichever came first. Cumulative incidences were estimated, adjusted for competing risk of death. These were compared to those observed in 579 patients admitted in the first wave, between February 24th and April 26th 2020, by means of Cox regression techniques adjusted for age, sex and weight. Results: In total 947 patients with COVID-19 were included in this analysis, of whom 358 patients were admitted to the ICU; 144 patients died (15%). The adjusted cumulative incidence of all thrombotic complications after 10, 20 and 30 days was 12% (95% confidence interval (CI) 9.8–15%), 16% (13–19%) and 21% (17–25%), respectively. Patient characteristics between the first and second wave were comparable. The adjusted hazard ratio (HR) for overall mortality in the second wave versus the first wave was 0.53 (95%CI 0.41–0.70). The adjusted HR for any thrombotic complication in the second versus the first wave was 0.89 (95%CI 0.65–1.2). Conclusions: Mortality was reduced by 47% in the second wave, but the thrombotic complication rate remained high, and comparable to the first wave. Careful attention to provision of adequate thromboprophylaxis is invariably warranted. Highlights: Half overall mortality in the second wave compared to first wave COVID-19 patients. Still high incidence of thrombotic complications in second wave. More subsegmental PE in second wave than in first wave.